1933 Haw. Sess. Laws 39, An Act Regulating the Sale, Transfer, and Possession of Firearms and Ammunition, § 8 - (:unkn) unknown (General Publisher, 1933)
Required license for concealed carry of pistol, firearm, or ammunition; prohibits issuance of license to felony convicts or mentally ill; violators subject to fine or imprisonment.
--
Keywords: CARRY - CONCEALED